Praktek Jual Beli Crypto Asset di Futures Market Perspektif Hukum Syariah - Fathudin; Nurul Fahmi, Muhammad (Program Studi Ekonomi Syariah Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Tarbiyatut Tholabah, 2023)
With his journey initially rejected, crypto assets began to be accepted internationally. In these few years to this day, it shows the process of changing international views on crypto assets. Although crypto assets are not considered as legal tender, Indonesia categorizes crypto assets as assets or commodities. This makes crypto assets under the regulation of the Commodity Futures Trading Supervisory Agency (BAPPEBTI) which is confirmed in Article 1 of the Regulation of the Minister of Trade of the Republic of Indonesia Number 99 of 2018 concerning General Policy for the Implementation of Crypto Assets Futures Trading (Crypto Assets), designated as commodities that can be subject to futures contracts. traded on futures exchanges. The purpose of this study is to examine and analyze the practice of buying and selling crypto assets on the Futures Market in terms of Sharia law. This research when viewed from the source of the data is normative legal research, namely research by examining library materials which are secondary data and also referred to as library research. The results of this study produce practices that occur in crypto asset trading contracts in the futures market, which are basically ribâl fadli practices. In addition, the legal prohibition of trading crypto assets in the futures market is due to the element of maisir. 'This illat appears as the option that small traders have is only one, which is to only sell at maturity. As a result, it automatically cancels the contract so that only the new price is left for the